Long-term outcomes of a case-control lung transplant cohort after SARS-CoV-2 infection - Hanna, Sandrine; Hallak, Rami; Leonard, Susanna M.; Morrison, Samantha; Peskoe, Sarah; Whitson, Jordan; Reynolds, John M.; Wolfe, Cameron R.; Ali, Hakim Azfar (Frontiers in Transplantation, 2025)
BackgroundRespiratory viruses can impact the allograft function in lung transplant recipients, but it is unknown if this occurs with SARS-CoV-2 infection. We studied the long-term outcomes of lung transplant recipients infected with SARS-CoV-2.MethodsThis single-center retrospective study compared lung transplant recipients with SARS-CoV-2 between June 2020 and April 2021 with a matched control group. Within the SARS-CoV-2 cohort, univariable associations between clinical factors and outcomes were tested. Changes in pulmonary function tests were analyzed. Primary endpoints included acute cellular rejection and all-cause mortality within 12 months.ResultsFifty-three lung transplant recipients were infected with SARS-CoV-2. The median age was 64 years. 29 (54.7%) were managed outpatient, and 24 (45.3%) required hospitalization, with 13 intensive care unit admissions. All-cause mortality was 24.5%. Within the SARS-CoV-2 cohort, older age was significantly associated with all-cause mortality (p-value 0.017) as was ICU admission (p = 0.009) and an A1C > 6.5 (p = 0.033). The mean change in FEV1 was −1.1% at 3 months with minimal change at 6 and 12 months (−2.6% and −1% respectively), all compared to baseline. Acute cellular rejection was identified in 13.7% of the SARS-CoV-2 cohort compared to 11.8% in the matched control group; it was not significantly associated with the infection status (p = 0.706). However, all-cause mortality was significantly associated with infection status (p = 0.019).ConclusionLong-term outcomes of SARS-CoV-2 in lung transplant recipients are widely variable. Within the SARS-CoV-2 cohort, all-cause mortality was 24.5%, and older age was significantly associated with mortality. We did not observe significant declines in FEV1 in this group.